Numerical study of two-phase turbulence nanofluid flow in a circular heatsink for cooling LEDs by changing their location and dimensions. (April 2023) - Mustafa, Jawed; Abdullah, M.M.; Ahmad, Mohammad Zaki; Husain, Shahid; Sharifpur, Mohsen
Abstract: The simulation of the turbulent flow of alumina/water nanofluid in a heatsink is presented in this article using the finite element method. The circular heatsink is used to cool the LEDs. A number of LEDs are placed under the heatsink so that an LED is placed in the middle and the rest are located at the bottom of the heatsink. By changing the distance of the side LEDs from the central one (D), the dimensions of the connection part of the LED to the heatsink (L), and the inlet velocity of the nanofluid (U), the values ​​of the heatsink temperature (T-HS), including the maximum, minimum and average temperature (T-Ave), as well as the outlet temperature (T-Out) of the nanofluid, are determined. The two-phase mixture approach is utilized to simulate nanofluid flow and the k-ε turbulence model is employed to model turbulent flow. The results demonstrate that changing the velocity of the nanofluid has the most effect on the T-Ave of the heatsink. As the velocity is increased, the T-Ave of the heatsink is reduced. Among the variables, L has the most effect on the maximum T-HS. The maximum T-HS is decreased with L. The most effect of changing the variables on the T-Out of the nanofluid is its velocity so that the T-Out is decreased with the velocity.